ASSESSMENT OF GENDER DIFFERENCES IN PRODUCTIVITY AMONG RURAL HOUSEHOLDS IN SOUTH WEST, NIGERIA - Nurudeen Afolabi Sofoluwe (Journal of Asian Rural Studies, 2019)
Increase in productivity across gender line is one of the necessary conditions for sustainable level of development in the rural areas. This study assessed the differences in productivity of men and women in rural households in Southwest, Nigeria. Average and marginal productivity of women and men were assessed. Gender-disaggregated data were obtained through structured questionnaires. Using multi stage sampling approach, a total of 197 and 148 men and women rural households were randomly sampled. Cobb Douglas production function was used to analyse differentials in productivity between women and men. The results showed that women have access to marginal and small pieces of land. Men with access to improved technology have significantly (p < 0.05) higher productivity per unit of most of the inputs available. Also, the result indicates that the estimated average productivities of women are signiﬁcantly lower than those of men. Furthermore, ownership of land has a significant positive influence on the estimated productivity of men more than women. Education which is another gender factor and a measure of human asset and managerial capacity significantly (p < 0.05) increased the productivity of men (β = 0.11, t = 3.04) and women (β = 0.07, t = 3.86). In order to raise productivity and impacts development agenda for the rural sector, it would be better for women to keep the variable resource in surplus rather than utilizing it in a fixed resource contrary to what is obtainable for men.